The Gateway to Computer Science Excellence
First time here? Checkout the FAQ!
x
+19 votes
2.9k views

Consider the following recurrence relation

$T(1)=1$

$T(n+1) = T(n)+\lfloor \sqrt{n+1} \rfloor$ for all $n \geq 1$

The value of $T(m^2)$ for $m \geq 1$ is

  1. $\frac{m}{6}\left(21m-39\right)+4$
  2. $\frac{m}{6}\left(4m^2-3m+5\right)$
  3. $\frac{m}{2}\left(3m^{2.5}-11m+20\right)-5$
  4. $\frac{m}{6}\left(5m^3-34m^2+137m-104\right)+\frac{5}{6}$
asked in Algorithms by Veteran (59.7k points) | 2.9k views
+1
hello..anybody idea about how to solve this recurrence ?
+3
For quick answer use  option rejection method.
0
How the general term of the series is calculated...how the last term comes as 'm' ?

5 Answers

+26 votes
Best answer

$T(m^2) = T(m^2-1) + \left\lfloor\sqrt{(m^2)} \right\rfloor$

               $= T(m^2 - 2) + \left\lfloor\sqrt{(m^2 - 1)} \right\rfloor +\left\lfloor\sqrt{(m^2)} \right\rfloor$

               $= T(m^2 - 3) + \left\lfloor\sqrt{(m^2 - 2)} \right\rfloor + \left\lfloor\sqrt{(m^2 - 1)} \right\rfloor +\left\lfloor\sqrt{(m^2)} \right\rfloor$

               $\vdots$

               $= T(1) + \left\lfloor\sqrt{(2)} \right\rfloor + \left\lfloor\sqrt{(3)} \right\rfloor + \ldots + \left\lfloor\sqrt{(m^2)} \right\rfloor$

               $= 3 \times 1 + 5 \times 2 +  \ldots + \left(2m - 1\right) \times (m-1) +m $

(We are taking floor of square root of numbers, and between successive square roots number of numbers are in the series $3,5,7 \dots$ like $3$ numbers from $1..4$, $5$ numbers from $5-9$ and so on).

We can try out options here or solve as shown at end:

Put $m = 5$, $T(25)  = 3 \times 1 + 5 \times 2 + 7 \times 3 + 9 \times 4 + 5 = 75$

  1. $59$
  2. $75$
  3. non-integer
  4. $297.5$


So, answer must be B.


$T(m^2) = 3 \times 1 + 5 \times 2 +  \dots + \left(2m - 1\right) \times (m-1) +m$
              $= m + \sum_i=1^{m-1} (2i+1). (i) $
              $= m + \sum_i=1^{m-1} 2i^2 + i$
              $= m + \frac{(m-1) .m .(2m-1)}{3} + \frac{(m-1)m}{2}$
              $= \frac{m}{6} \left(6 + 4m^2 -2m -4m + 2 + 3m - 3\right)$
              $= \frac{m}{6} \left(4m^2 -3m + 5\right) $

[Sum of the first $n$ natural numbers $=\frac{n. (n+1)}{2}.$ 

Sum of the squares of first $n$ natural numbers $ = \frac{n. (n+1). (2n+1)}{6}.$]

answered by Veteran (370k points)
edited by
+4
why 3*1+5*2...........?
+8
Floor of squareroot(1), squareroot(2) and squareroot(3) is 1. Therefore, 3*1 and so on..
0
ok :)
0
Very good analysis. :) Thank You.
0
Edit it .... i am nt gd in latex ...
+17 votes

we can write this recurrence as T(n)=T(n-1)+√n 

Now we can apply master theorem for subtract and conquer 

here, a=1,b=1 f(n)=O(√n )

By case 2 of  subtract and conquer T(n)=O(n^1.5)

if we take n=m^2

T(m^2)=O(m^3),and which is tighter upper bound of  option B.

see below for subtract and conquer of master theorem.

https://www.eecis.udel.edu/~saunders/notes/recurrence-relations.pdf

answered by Active (4.4k points)
+1
Nice source of information!
0

@jatin saini How did you write this RR from given RR - T(n)=T(n-1)+√n 

Did you put n=n-1 or subtract -1 from both sides?

0
Is this subtract conquer method is authentic?
+5 votes

T(1)=1

T(2)=T(1)+⌊√2⌋=1+1=2

T(3)=T(2)+⌊√3⌋=2+1=3

T(4)=T(3)+⌊√4⌋=3+2=5

....... so on 

now find T(m2)

take m=2 so T(m2) =T(4)

now check options ,  only option B give value 5 which is equals to T(4)

so ans is B

answered by Active (2.5k points)
0
@Gate Ranker18

Nopes , even option A will be also true , if u will do like this. So u can not say like this .
0
Yes exactly option A is also matching when m=2 and for m=3 also.
+1 vote

Using Integration bounds technique we can get approximate answer.

Integration bound method is explained in detail here(page 11, theorem 9.3.1). 

$T(n) = T(n-1) + \left \lfloor \sqrt{n} \right \rfloor , n > 1$

Unrolling it gives,

$T_n = \sum_{k = 1}^{n} \left \lfloor \sqrt{k} \right \rfloor$

But, because $k - \left \lfloor k \right \rfloor < 1$

$\sum_{k = 1}^{n} \sqrt{k} - n \le T_n \le \sum_{k = 1}^{n} \sqrt{k}$

So, Let's find $S_n = \sum_{k = 1}^{n} \sqrt{k}$

Integration bound theorem: if $f$ is non decreasing function, $S = \sum_{k = 1}^{n} f(k)$ and $I = \int_{1}^{n} f(x) * dx$ then $I + f(1) \le S \le I + f(n)$.

$\frac{2}{3}*n^{\frac{3}{2}} - \frac{2}{3} + 1 \le S_n \le \frac{2}{3}*n^{\frac{3}{2}} - \frac{2}{3} + \sqrt{n}$

$\frac{2}{3}*n^{\frac{3}{2}} + \frac{1}{3} - n \le T_n \le \frac{2}{3}*n^{\frac{3}{2}} - \frac{2}{3} + \sqrt{n}$

Taking $n = m^2$

$\frac{2}{3}*m^3 - m^2  + \frac{1}{3} \le T_{m^2} \le \frac{2}{3}*m^3 - \frac{2}{3} + m$

Closet match is B.

answered by Active (2k points)
edited by
0 votes
One easy way to solve this is to try putting different 
values of m.

For example, we know T(1) = 1. If we put m = 1, only A
and B satisfy the result.

m = 2

T(2) = T(1) + 1 = 2
T(3) = T(2) + 1 = 3
T(4) = T(3) + 2 = 5

Both A & B produce 5

m = 3
T(9) = T(4) + 2*5 + 1 = 5 + 10 + 1 = 16
Both A & B produce 16

m = 4
T(16) = T(9) + 3*7 + 1 = 16 + 21 + 1 = 38
Only B produces 38, A produces 34 which doesn't match

Source:geeksforgeeks

answered by Active (3.5k points)
Answer:

Related questions



Quick search syntax
tags tag:apple
author user:martin
title title:apple
content content:apple
exclude -tag:apple
force match +apple
views views:100
score score:10
answers answers:2
is accepted isaccepted:true
is closed isclosed:true

44,492 questions
49,942 answers
165,709 comments
65,911 users